2005
DOI: 10.1103/physrevd.72.034006
|View full text |Cite
|
Sign up to set email alerts
|

Even- and odd-parity charmed meson masses in heavy hadron chiral perturbation theory

Abstract: We derive mass formulae for the ground state, J P = 0 − and 1 − , and first excited even-parity, J P = 0 + and 1 + , charmed mesons including one loop chiral corrections and O(1/m c ) counterterms in heavy hadron chiral perturbation theory. We show that including these counterterms is critical for fitting the current data. We find that certain parameter relations in the parity doubling model are not renormalized at one loop, providing a natural explanation for the observed equality of the hyperfine splittings … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(131 citation statements)
references
References 56 publications
5
123
3
Order By: Relevance
“…Such predictions have been made for conventional mesons with parity doubling [5], using heavy quark effective theory [27,28] or for B ( * ) K molecules in a variety of publications [11][12][13][14]29]. Here, we update the latter class of works, and especially identify radiative decays as the probably most promising discovery modes of the bottom-partners of the D * s0 and D s1 .…”
Section: Introductionmentioning
confidence: 99%
“…Such predictions have been made for conventional mesons with parity doubling [5], using heavy quark effective theory [27,28] or for B ( * ) K molecules in a variety of publications [11][12][13][14]29]. Here, we update the latter class of works, and especially identify radiative decays as the probably most promising discovery modes of the bottom-partners of the D * s0 and D s1 .…”
Section: Introductionmentioning
confidence: 99%
“…level [6]. However, it is not clear if the parity doubling is a consequence of quantum chromodynamics (QCD).…”
Section: Introductionmentioning
confidence: 99%
“…Our work showed that including the counterterms is critical for fitting the current data on charm mesons. We also found that certain parameter relations in the parity doubling model are not renormalized at one loop, providing a natural explanation for the equality of the hyperfine splittings of ground state and excited doublets [90].…”
Section: Even-parity Excited Charmed Strange Mesonsmentioning
confidence: 94%